2014
DOI: 10.1128/jvi.00063-14
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus BALF3 Has Nuclease Activity and Mediates Mature Virion Production during the Lytic Cycle

Abstract: Epstein-Barr virus (EBV) lytic replication involves complex processes, including DNA synthesis, DNA cleavage and packaging, and virion egress. These processes require many different lytic gene products, but the mechanisms of their actions remain unclear, especially for DNA cleavage and packaging. According to sequence homology analysis, EBV BALF3, encoded by the third leftward open reading frame of the BamHI-A fragment in the viral genome, is a homologue of herpes simplex virus type 1 UL28. This gene product i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 91 publications
0
28
0
Order By: Relevance
“…The cells expressing GFP-BALF3 exhibited more H2AX phosphorylation than the mock and pEGFP-C1 transfections, detected by immunofluorescence staining with an antibody specific to γH2AX (Figure 1G), suggesting that EBV BALF3 could induce DSBs. Moreover, a recent study in our laboratory has shown that alanine substitution of the glycine residue at amino acid 624 of EBV BALF3 results in reduced endonucleolytic activity [58]. Therefore, the coding region of BALF3 in pEGFP-C1-BALF3 was mutated by replacement of glycine 624 with alanine, with the result that the occurrence of micronuclei and H2AX phosphorylation induced by the G624A mutant was reduced to a significant extent, compared to the wild-type transfection (Figure 1C, D and G), confirming that EBV BALF3 could generate chromosome breakage and loss and DSBs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cells expressing GFP-BALF3 exhibited more H2AX phosphorylation than the mock and pEGFP-C1 transfections, detected by immunofluorescence staining with an antibody specific to γH2AX (Figure 1G), suggesting that EBV BALF3 could induce DSBs. Moreover, a recent study in our laboratory has shown that alanine substitution of the glycine residue at amino acid 624 of EBV BALF3 results in reduced endonucleolytic activity [58]. Therefore, the coding region of BALF3 in pEGFP-C1-BALF3 was mutated by replacement of glycine 624 with alanine, with the result that the occurrence of micronuclei and H2AX phosphorylation induced by the G624A mutant was reduced to a significant extent, compared to the wild-type transfection (Figure 1C, D and G), confirming that EBV BALF3 could generate chromosome breakage and loss and DSBs.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effect of BALF3 on uninfected cells, BALF3 was expressed alone in NPC cells and these were examined for genetic alterations using several methods, showing that the BALF3 expression led to the induction of micronuclei, DNA strand breaks and genomic CNAs (Figure 1, 2 and 3). BALF3 has nuclease activity and the BALF3-mediated nucleolytic reaction occurs not only in the terminal repeats of the EBV genome, which contain cleavage/packaging signals, but also in vitro in plasmid DNA without the terminal repeat sequence [58]. Similarly, nonspecific cleavage also has been reported for the terminases of human cytomegalovirus (HCMV) and bacteriophage T4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein complex that docks or interacts with the capsid portal protein consists of the heterotrimeric viral terminase. Terminases of DNA bacteriophages have been well described (2,3), and those of several members of the Herpesviridae, including herpes simplex virus 1 (HSV-1) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), human cytomegalovirus (HCMV) (15)(16)(17)(18)(19)(20)(21), Epstein-Barr virus (EBV) (22), and varicella-zoster virus (VZV) (23)(24)(25), are under investigation.…”
mentioning
confidence: 99%